2020
DOI: 10.1080/2330443x.2020.1777915
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Approach to Measuring Vote Elasticity and Competitiveness

Abstract: The recent wave of attention to partisan gerrymandering has come with a push to refine or replace the laws that govern political redistricting around the country. A common element in several states' reform efforts has been the inclusion of competitiveness metrics, or scores that evaluate a districting plan based on the extent to which district-level outcomes are in play or are likely to be closely contested. In this article, we examine several classes of competitiveness metrics motivated by recent reform propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Compactness, at levels comparable to those observed in humanmade plans, is an automatic consequence of the spanning-tree-based recombination step. For more information about the Markov chain used here, see (DeFord, Duchin, and Solomon 2019).…”
Section: Utah and The "Utah Paradox"mentioning
confidence: 99%
“…Compactness, at levels comparable to those observed in humanmade plans, is an automatic consequence of the spanning-tree-based recombination step. For more information about the Markov chain used here, see (DeFord, Duchin, and Solomon 2019).…”
Section: Utah and The "Utah Paradox"mentioning
confidence: 99%
“…Therefore, to study redistricting, researchers have developed ensemble methods [10,25,33,48,57] that generate huge quantities of legal district plans to explore the exponentially large space of feasible maps. Such techniques are commonly used to detect gerrymandering [27,37,39,50] or to study the impact of different redistricting rules on the distribution of outcomes [32,34]. However, even under neutral ensembles, the natural geographic segregation among partisan voters can create skewed political outcomes [18,25].…”
Section: Related Workmentioning
confidence: 99%
“…There are many proposed definitions of (un)fairness metrics in redistricting such as the efficiency gap [71], the mean-median gap [79], partisan-symmetry [80], competitiveness [34], and most simply, proportionality. Such metrics can be used as the objective function of an optimization algorithm to generate district maps with (un)fair outcomes [48,53,73].…”
Section: Related Workmentioning
confidence: 99%
“…There are districts like that in real life, but it turns out requiring districts to be roughly round 8 is also not sufficient to prevent strong partisan gerrymandering. Ensemble methods have also shown that rules which are facially neutral to party, like maximization of the number of competitive districts, can introduce partisan bias [8]. What's more, the ensemble method speaks to much more than the number of seats each party winsthat's just one statistic attached to the maps in the ensemble.…”
Section: What's Next?mentioning
confidence: 99%